Meaning and view of ethnomathematics in the tales of Malay storytellers - Hamdan, Rahimah; Abdullah, Shahrum
This paper presents the fundamental of understanding mathematics in traditional Malay culture. Western scholars has labeled the Malay community as the people who are not capable to evaluate the accuracy of mathematics. On the other hand, its obscure to accept that the Malay mathematical ideas merely based on their close observation to the nature. In this respect, the study of ethnomathematic is relevant to analyze the mathematical ideas of traditional peoples initially used in the discipline of Anthropology. Literary work is a reflection of mind and culture of society. Thus, this paper will analyze three works of Malay oral literature i.e.The Tales of Awang Sulung Merah Muda (Hikayat Awang Sulung Merah Muda), The Tales Of Terung Pipit (Hikayat Terung Pipit) and Raja Donai Bahtera Kulit Kacang which basically presented by the Malay storytellers. Each set of Malay mathematical ideas will be interpreted according to the metric system parallel with the explanation of Malay thought and world view. Several mathematical techniques are used actively in the text,for instance the determination of the length, weight, predictable time and some other calculations. Indirectly, this analysis will prove that the Malay community are capable in assembling their mathematical ideas perfectly and harmonize with their culture perception.